Effect of Osmotic Pressure on Migration Behavior of nZnO in GCLs - Ping Yang; Tao Jiang; Youlong Zhang; Zhicheng Li (Advances in Civil Engineering)
The migration of zinc oxide nanoparticles (nZnO) in geosynthetic clay liners (GCLs) under different osmotic pressures was conducted using a self-developed geosynthetic clay liner osmometer. The effects of the osmotic pressure on the migration behavior of nZnO in GCLs were analyzed. The results showed that, with an increase of osmotic pressure, the retention rate of nZnO increased greatly, the particle size increased, the stability of the soliquoid declined, GCLs pores were compressed, the infiltration coefficient of GCLs reduced, and the interception effect of GCLs on nZnO particles strengthened. The two-site model can simulate the migration behavior of nZnO in GCLs very well. The correlativity between the maximum migration distance (Lmax) of nZnO in GCLs and the osmotic pressure was negative.